2019
DOI: 10.3390/cells8111398
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of STAT3 in Shaping Glioblastoma Immune Microenvironment

Abstract: Glioblastoma belongs to the most malignant intracranial tumors characterized by indispensable growth and aggressiveness that highly associates with dismal prognosis and therapy resistance. Tumor heterogeneity that often challenges therapeutic schemes is largely attributed to the complex interaction of neoplastic cells with tumor microenvironment (TME). Soluble immunoregulatory molecules secreted by glioma cells attract astrocytes, circulating stem cells and a range of immune cells to TME, inducing a local prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 70 publications
0
70
0
Order By: Relevance
“…Moreover, profound immunosuppression occurs in the tumor microenvironment, particularly in the context of cell-mediated immunity [31], which is driven by an array of cytokines, such as prostaglandin E2, transforming growth factor beta (TGF-β), matrix metallopeptidase 9, IL-10, programmed death-ligand 1 (PD-L1), granulocyte colony stimulating factor, VEGF, and S100A4 [18,31,33,52,53]. At a mechanistic level, most proposed pathways to mediate immunosuppression in GBM are those involving signal transducer and activator of transcription 3 (STAT-3) [54,55], phosphoinositide 3 kinase, Ras-mitogen-activated protein kinase, wingless-related integration site/β-catenin, and indolamine 2, 3-dioxygenase [56].…”
Section: Tans In Glioma Progressionmentioning
confidence: 99%
“…Moreover, profound immunosuppression occurs in the tumor microenvironment, particularly in the context of cell-mediated immunity [31], which is driven by an array of cytokines, such as prostaglandin E2, transforming growth factor beta (TGF-β), matrix metallopeptidase 9, IL-10, programmed death-ligand 1 (PD-L1), granulocyte colony stimulating factor, VEGF, and S100A4 [18,31,33,52,53]. At a mechanistic level, most proposed pathways to mediate immunosuppression in GBM are those involving signal transducer and activator of transcription 3 (STAT-3) [54,55], phosphoinositide 3 kinase, Ras-mitogen-activated protein kinase, wingless-related integration site/β-catenin, and indolamine 2, 3-dioxygenase [56].…”
Section: Tans In Glioma Progressionmentioning
confidence: 99%
“…In the emerging era of immunotherapy, the concept of the tumor microenvironment (TME) [14,15] and immune checkpoint (IC) [16] is vital in developing oncology research. Since the rollout of the first United States (US) Food and Drug Administration (FDA)-approved immune checkpoint inhibitors (ICIs) in 2010, existing ICIs include the following types: (1) anti-cytotoxic T-lymphocyte antigen 4 (CTLA-4) antibodies, including ipilimumab; (2) anti-programmed cell death-1 (anti-PD-1)/programmed cell death ligand-1 (PD-L1) antibodies, including pembrolizumab and nivolumab.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we further demonstrated the valuable therapeutic efficacy of ODZ10117 in both in vitro and in vivo models of glioblastoma and GSCs. According to recent studies, aberrantly activated STAT3 signaling is considered a paradigm for tumor initiation and malignancy, radiochemoresistance, and recurrence due to observation in many types of cancers [4,11,31]. These correlations are mainly related to the functions of STAT3 in promoting the migration and invasion and maintaining stem cell properties of cancer cells, which indicates that STAT3 is an attractive molecular target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It can be activated directly or indirectly by receptor-associated and non-receptor-associated tyrosine kinases such as Janus kinases (JAKs), Src family kinases and Bcr-Abl kinase [5,6]. Accumulated evidence demonstrated that constitutively activated STAT3 is observed in various types of tumor-derived cell lines and tumor tissues, including diverse solid and hematologic cancers [7][8][9][10][11]. Constitutively activated STAT3 is closely related to oncogenic signaling, recurrence and drug resistance that increases cancer aggressiveness and malignancy by promoting the survival, proliferation, invasion, and metastasis of cancer cells and maintenance of cancer stem cell (CSC) properties in a wide range of cancers in the inflammation-associated tumor microenvironment [5,6].…”
Section: Introductionmentioning
confidence: 99%